Special series on the role of the microbiome in reproduction and fertility - S M O'Mahony; P Comizzoli (Bioscientifica, 2023)
Many parts of the animal and human body host groups of bacteria, viruses, and fungi that together are known as the microbiome. Microbiomes do not cause disease but are important for the healthy working of many systems in the body, including for reproduction and fertility. While the microbiome that lives in a reproductive tract play the most direct role, microbiomes from other areas of the body may also affect reproductive health. However, not much is known about how these groups of microorganisms regulate fertility as well as the health of parents and offspring and help animals to cope with environmental changes. Furthermore, compared to the large amount of research in laboratory species and humans, there is less information about domestic or wild animal species. This special series of Reproduction and Fertility on microbiomes is aimed at filling this gap with articles from experts highlighting important evidence in reproductive microbiomes, current research gaps, and new directions.